1998
DOI: 10.1007/s004230050144
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid carcinoma in intrathoracic goiter

Abstract: A thoracic approach is more frequently needed for treatment of intrathoracic thyroid carcinoma as it offers a greater chance of radical excision and better control of intraoperative bleeding. Histologically, thyroid carcinoma in intrathoracic goiter is often anaplastic or rare and has a poor long-term survival rate when compared to cervical forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 9 publications
0
19
1
1
Order By: Relevance
“…One of the most common symptoms of compression from retrosternal goitres is dyspnea. Both our patients presented with these symptoms and given the slow growth of the mass and typical age of these patients these symptoms are often mistaken for diagnoses such as chronic obstructive pulmonary disease or cardiac failure [3]. The presence of dyspnea and history of prior thyroid resection, as in case two, should alert the physician of a recurrent goitre.…”
Section: Discussionmentioning
confidence: 80%
“…One of the most common symptoms of compression from retrosternal goitres is dyspnea. Both our patients presented with these symptoms and given the slow growth of the mass and typical age of these patients these symptoms are often mistaken for diagnoses such as chronic obstructive pulmonary disease or cardiac failure [3]. The presence of dyspnea and history of prior thyroid resection, as in case two, should alert the physician of a recurrent goitre.…”
Section: Discussionmentioning
confidence: 80%
“…The majority of cervical and retrosternal goiters are extensions and enlargement of thyroid gland. However, in some studies the prevalence of thyroid cancer has been reported up to 23% in retrosternal goiter (5).…”
Section: Discussionmentioning
confidence: 99%
“…Focal or diffuse uptake of thyroid can be seen in various benign and malignant conditions, including thyroid carcinoma, metastatic tumor, thyroiditis, multinodular goiter and nodular hyperplasia [15]. Acute suppurative thyroiditis may occur in intrathoracic ectopic thyroid [16] and cancer can occur in 3% to 10% of intrathoracic ectopic thyroid [2,17]. Although there is no consensus for the optimal therapeutic strategy, surgical treatment can be considered based on some parameters, such as size, local symptoms, and complication of the mass (ulceration, bleeding, cystic degeneration, malignant transformation) [6,18].…”
Section: Discussionmentioning
confidence: 99%